The Effect of Individual Characteristics, Organizational Climate, and Job Satisfaction on Employee Performance at Mason Elephant Park & Lodge Gianyar - Putra, I Wayan Juliantara; Saraswati, Ni Putu Ayu Sintya; Utami, Ni Made Satya (EMAS, 2026)
Human resources always play an active and dominant role in every organizational and business activity, because humans are the planners, actors, and determinants of the realization of organizational and business goals. Human resources are one of the most decisive factors in the success or failure of an organization or company. This study aims to determine and analyze the influence of individual characteristics, organizational climate, and job satisfaction on employee performance at Mason Elephant Park & Lodge Gianyar. The population in this study was employees at Mason Elephant Park & Lodge Gianyar. The sample in this study consisted of 59 respondents, using a saturated sampling method where the entire population was used as the sample. The analysis used in this study was multiple linear regression analysis processed using the SPSS version 25.0 program. Based on the analysis results, this study shows that individual characteristics, organizational climate, and job satisfaction each have a significant positive effect on employee performance at Mason Elephant Park & Lodge Gianyar. Suggestions for further research include developing this study by adding variable variations such as job training, leadership style, and knowledge sharing.